2022
DOI: 10.3389/fsurg.2022.837008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Efficacy and Safety of Modified Transfrontal Puncture Drainage in Hypertensive Basal Ganglia Hemorrhage Patients

Abstract: ObjectiveThe study aimed to explore the efficacy and safety of modified transfrontal puncture drainage in patients with hypertensive basal ganglia hemorrhage.MethodsThe study enrolled 102 patients with hypertensive basal ganglia hemorrhage who received treatment at our hospital between April 2020 and June 2020. They were divided into a control group (51 cases, burr hole evacuation of intracranial hematoma) and a study group (51 cases, modified transfrontal puncture drainage) using the random number table metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…The study by Zhang et al [27] pointed out that the admission GCS score was an influencing factor for patients with hypertensive basal ganglia hemorrhage. Deng [28] showed that admission GCS score and age were influencing factors for the prognosis of patients with hypertensive intracerebral hemorrhage in the basal ganglia region after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Zhang et al [27] pointed out that the admission GCS score was an influencing factor for patients with hypertensive basal ganglia hemorrhage. Deng [28] showed that admission GCS score and age were influencing factors for the prognosis of patients with hypertensive intracerebral hemorrhage in the basal ganglia region after surgery.…”
Section: Discussionmentioning
confidence: 99%